2017
DOI: 10.1177/0954411917738805
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical response of a polyetheretherketone femoral knee implant under a deep squatting loading condition

Abstract: The current study was designed to investigate the mechanical response of a polyetheretherketone-on-polyethylene total knee replacement device during a deep squat. Application of this high-demand loading condition can identify weaknesses of the polyetheretherketone relative to cobalt-chromium. This study investigated whether the implant is strong enough for this type of loading, whether cement stresses are considerably changed and whether a polyetheretherketone femoral component is likely to lead to reduced per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…It is postulated that the higher stiffness of CoCr compared to PEEK also gives the potential for higher local stresses in the cement–CoCr implant interface as the femoral component is less compliant. Previous studies have shown the stiff CoCr component to generate high stress peaks in the cement underneath the proximal anterior flange [ 24 , 25 , 26 , 37 ]. Many small cracks were visible in this region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is postulated that the higher stiffness of CoCr compared to PEEK also gives the potential for higher local stresses in the cement–CoCr implant interface as the femoral component is less compliant. Previous studies have shown the stiff CoCr component to generate high stress peaks in the cement underneath the proximal anterior flange [ 24 , 25 , 26 , 37 ]. Many small cracks were visible in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Many small cracks were visible in this region. Analysis of these small cracks was beyond the scope of this study but there is potential for these small cracks to grow, which may further increase cement damage in the anterior flange [ 20 , 24 , 25 ]. The numbers of cracks in cement at the anterior flange and posterior chamfer areas of the cement mantle were similar in both implants; however, there was a greater number of cracks in the PEEK–cement interface in the anterior chamfer and the posterior flange compared to the CoCr–cement interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of implant wear testing, implant fixation, and joint stability analysis, there are other more challenging activities commonly performed in daily living that might be of particular interest (Hartmann et al, 2013). Clinical, experimental, and computational studies have clearly reported increased complication risk and wear rate under high contact stress conditions (Kang et al, 2008;O'Brien et al, 2015;de Ruiter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%